Prevalence of brucellosis in cattle slaughtered in a local abattoir in Hammanskraal, South Africa - Van Heerden, Henriette (University of Pretoria, 2022)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2020.